Pertumbuhan Kedelai pada Kondisi Cekaman Salinitas dengan Pemberian Ekstrak Kulit Buah Nanas (Ananas comosus L) - Maman Suryaman; Fitri Kurniati; Hani Khaerunisa (Politeknik Negeri Lampung., 2022)
This study aims to determine the potential of pineapple peel extract in improving soybean growth due to salinity stress. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Siliwangi University from October to November 2020. This research was conducted experimentally using a Randomized Block Design with a factorial pattern. Factor 1 is salinity stress with 3 levels (NaCl 0% = EC 0.56 mS cm-1, NaCl 0.5% = EC 7.59 mS cm-1, and NaCl 1% = EC 8.25 mS cm-1), factor 2 is the concentration of pineapple peel extract (0%, 1%, and 2 %), with 3 replicatons. The data observed consisted of: leaf area, relative water content of leaves, leaf chlorophyll content, and plant dry weight. Data were analyzed by Anova and continued with Duncan's test at 5% α level. The results showed that the effect of interaction between salinity stress and pineapple peel extract on soybean growth was not significant. Salinity stress reduced leaf area, relative water content of leaves, chlorophyll content, and dry weight of soybean plants, while pineapple peel extract could increase leaf area, chlorophyll content and dry weight of soybean plants. Thus, pineapple peel extract has the potential to improve soybean growth under conditions of salinity stress. Keywords: growth, pineapple peel extract, salinity stress, soybean.